2007
DOI: 10.1029/2006jb004544
|View full text |Cite
|
Sign up to set email alerts
|

Stress, strain, and B‐type olivine fabric in the fore‐arc mantle: Sensitivity tests using high‐resolution steady‐state subduction zone models

Abstract: [1] Shear-wave splitting observations at several subduction systems show trench-parallel fast directions in the fore-arc mantle. The presence of B-type olivine fabric in the mantle wedge may provide an explanation for this pattern of anisotropy under low-temperature and hydrated conditions. Sensitivity tests are shown that provide insights into the distribution and magnitude of B-type fabric using two-dimensional, highresolution, kinematic-dynamic subduction zone models. These models include a wet olivine rheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 73 publications
7
86
1
1
Order By: Relevance
“…There are large volumes of water releasing upwards from dehydration of the subducting oceanic crust and sediments to the fore-arc mantle wedge, and the fore-arc temperature is always low due to the sink of the cold subducting Pacific plate. Kneller et al (2007) suggested that the best candidate region of the mantle wedge for B-type conditions with sufficient finite strain accumulation is in the central region of the fore-arc mantle. Therefore, our obtained trench-parallel anisotropy in the central part of the fore-arc mantle wedge is probably caused by simple corner flow geometry when the B-type olivine fabric dominates in the region.…”
Section: Discussionmentioning
confidence: 99%
“…There are large volumes of water releasing upwards from dehydration of the subducting oceanic crust and sediments to the fore-arc mantle wedge, and the fore-arc temperature is always low due to the sink of the cold subducting Pacific plate. Kneller et al (2007) suggested that the best candidate region of the mantle wedge for B-type conditions with sufficient finite strain accumulation is in the central region of the fore-arc mantle. Therefore, our obtained trench-parallel anisotropy in the central part of the fore-arc mantle wedge is probably caused by simple corner flow geometry when the B-type olivine fabric dominates in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been explored to decouple kinematically the two converging plates. A first set is based on kinematic assumptions, such as imposing: free slip along the boundary (Furukawa, 1993); rigid and motionless fore-arc lithosphere (Peacock and Hyndman, 1999;van Keken et al, 2002), or a progressive kinematic coupling between the upper lithosphere sublayer and the subducting slab (Kneller et al, 2005(Kneller et al, , 2007Syracuse et al, 2010). Another approach aims at simulating low strength/low shear along the interplate boundary, by either assigning low viscosities to the interface nodes (Billen and Gurnis, 2001;Kelemen et al, 2003;Wada et al, 2008;Wada and Wang, 2009), or limiting shear stress (Zhong and Gurnis, 1995;van Hunen et al, 2002), or impeding fore-arc deformation if predicted to occur in the brittle domain, itself being delimited by a predetermined temperature (Conder, 2005;Syracuse et al, 2010).…”
Section: Modelling the Subduction Interplate In Simulations Of Convermentioning
confidence: 99%
“…This could be avoided by inclusion of physically realistic self-limiting processes, such as a transition to higher stress flow mechanisms or the inclusion of viscous dissipation (e.g. Kneller et al, 2007;Wada et al, 2008). For the ease of the numerical comparison it is simpler and sufficient to truncate the viscosity at a fixed maximum Á max .…”
Section: Governing Equationsmentioning
confidence: 99%
“…The modification could have impacts on thermal structure that are significantly larger than differences between simulation results from different codes. These factors include the dynamical effects of mineralogical phase changes including the likely serpentization of the wedge corner (Hyndman and Peacock, 2003;Gorczyk et al, 2007), melting and melt transport (Katz et al, 2007;Cagnioncle et al, 2007), and threedimensional effects (Kneller et al, 2007;Behn et al, 2007).…”
Section: Introductionmentioning
confidence: 99%